2021
DOI: 10.3390/plants10030593
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Finger-Homeodomain Transcriptional Factors (ZF-HDs) in Wheat (Triticum aestivum L.): Identification, Evolution, Expression Analysis and Response to Abiotic Stresses

Abstract: Zinc finger-homeodomain transcriptional factors (ZF-HDs), a kind of plant-specific transcription factor, play important roles in plant growth, development and various stress responses. In this study, the genome-wide analysis of the ZF-HD gene family was performed in wheat. A total of 37 TaZF-HD genes were identified in T. aestivum and classified into six groups. The results of a synteny analysis showed that gene replication events contributed to the expansion of the TaZF-HD gene family. The TaZF-HD paralogous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 41 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…Besides the regulatory role in the growth and development, some ZF-HD genes may play a vital role in response to abiotic stresses such as drought, heat, cold, and salt [ 76 ]. Recent studies indicate that ZF-HD is induced by cold stress, NaCl, and PEG in wheat [ 77 ]. Consistent with all previous reports, we also found the flower gynoecium in CsWUS-OE was smaller than that in WT.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the regulatory role in the growth and development, some ZF-HD genes may play a vital role in response to abiotic stresses such as drought, heat, cold, and salt [ 76 ]. Recent studies indicate that ZF-HD is induced by cold stress, NaCl, and PEG in wheat [ 77 ]. Consistent with all previous reports, we also found the flower gynoecium in CsWUS-OE was smaller than that in WT.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter region analysis of the MdZF-HD genes identified several cis -elements related to phytohormones and abiotic stresses ( Figure 5 ). Based on the previous studies, ZF-HD family genes were mostly found to participate in the responses to abiotic stresses ( Tan and Irish, 2006 ; Figueiredo et al, 2012 ; Wang et al, 2016 ; Liu et al, 2021 ). For instance, ZF-HD family genes from Arabidopsis, tomato, cucumber, and also apple were shown to be up-regulated by various kinds of stress conditions, such as drought, salt, cold, heat, and phytohormones including GA and ABA ( Shan et al, 2012 ; Zhang et al, 2015 ; Khatun et al, 2017 ; Shalmani et al, 2019 ; Lai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was possibly due to the higher expression of several genes that regulate protection against oxidative stress and lipid metabolism, and thus determining cell membrane stability under stress conditions ( Campo et al, 2014 ). The zinc finger super family transcription factors regulate multiple aspects of plant development and abiotic stress tolerance ( Liu et al, 2021 ). Zinc Finger 2 (SlZF2) is rapidly induced by drought in cultivated tomatoes ( Solanum lycopersicum ), and its ectopic expression provides tolerance against salinity stress ( Hichri et al, 2014 ).…”
Section: Influence Of Reactive Oxygen Species-antioxidative System On Plant Processesmentioning
confidence: 99%